Large meta-analysis of genome-wide association studies identifies five loci for lean body mass - M. Carola Zillikens (Nature Portfolio, 2017)
Lean body mass is a highly heritable trait and is associated with various health conditions. Here, Kiel and colleagues perform a meta-analysis of genome-wide association studies for whole body lean body mass and find five novel genetic loci to be significantly associated.